2010
DOI: 10.1136/bjo.2009.159541
|View full text |Cite
|
Sign up to set email alerts
|

Transcleral delivery of triamcinolone acetonide and ranibizumab to retinal tissues using macroesis

Abstract: Successful delivery of ranibizumab and triamcinolone acetonide can be achieved with macroesis in preclinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In many cases, existing drugs need to be reformulated to confer an electric charge so that they can be utilized within the system. To resolve these problems, Macroesis™ (Buckeye Pharmaceuticals, Beachwood, OH, U.S.) propose using an alternating current instead of DC [159,160].…”
Section: Iontophoresismentioning
confidence: 99%
“…In many cases, existing drugs need to be reformulated to confer an electric charge so that they can be utilized within the system. To resolve these problems, Macroesis™ (Buckeye Pharmaceuticals, Beachwood, OH, U.S.) propose using an alternating current instead of DC [159,160].…”
Section: Iontophoresismentioning
confidence: 99%
“…4,56 Animal studies have shown successful administration of triamcinolone acetonide and ranibizumab through fullthickness ocular tissue in rabbits. 57,58 OcuPhor, EyeGate, and Visulex are the few ocular iontophoresis systems, which have been developed recently. 59,60,64 Encapsulated cell technology Encapsulated cell technology, developed by Neurotech Pharmaceuticals, is one of the latest innovations in posterior segment sustained drug delivery systems.…”
Section: Suprachoroidal Drug Delivery Via Itrack Microcathetermentioning
confidence: 99%
“…Transscleral delivery of triamcinalone and Lucentis has been successfully applied in animal models using electrically facilitated macroesis methodology [124]. Dexamethasone has been shown to suppress the release of various pro-inflammatory and pro-angiogenic cytokines from retinal pericytes [125].…”
Section: What Future Frontiers and Direction Are Available For Mtmentioning
confidence: 99%